Transcatheter Mitral Valve Replacement with Dedicated Devices - Joe Aoun; Michael J. Reardon; Sachin S. Goel (Methodist DeBakey Cardiovascular Journal)
Mitral regurgitation is the most common form of valvular heart disease. The anatomy and pathophysiology of mitral valve regurgitation are very complex, and dedicated devices are required for transcatheter mitral valve replacement in patients with a high or prohibitive surgical risk. In the United States, all transcatheter mitral valve replacement devices are still being studied and are not yet approved for commercial use. Early feasibility studies have demonstrated good technical success and short-term outcomes, but larger samples and longer-term outcomes still need to be assessed. Furthermore, significant advances in device technology, delivery systems, and implantation techniques are essential to avoid left ventricular outflow tract obstruction, and valvular and paravalvular regurgitation as well as ensuring good anchoring of the prosthesis.